2016
DOI: 10.1016/j.jfoodeng.2015.10.028
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between in-line measurements of tomato ketchup shear viscosity and extensional viscosity

Abstract: Access to the published version may require subscription. N.B. When citing this work, cite the original published paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…Yield stress is an important characteristic in many food systems such as in ketchup and mayonnaise (Berta et al, 2016) however, the The stress at which this change occurs is the yield stress and it was calculated by the intersection of two linear fitting curves measurement of yield stress is not straight forward. Many difficulties such as wall slippage arise during measurement and a detailed discussion on these difficulties has been discussed elsewhere (Barnes, 1995;Walls, Caines, Sanchez, & Khan, 2003).…”
Section: Yield Stress In Shear Rheology (Viscometry and Puv 1 Pd)mentioning
confidence: 99%
See 2 more Smart Citations
“…Yield stress is an important characteristic in many food systems such as in ketchup and mayonnaise (Berta et al, 2016) however, the The stress at which this change occurs is the yield stress and it was calculated by the intersection of two linear fitting curves measurement of yield stress is not straight forward. Many difficulties such as wall slippage arise during measurement and a detailed discussion on these difficulties has been discussed elsewhere (Barnes, 1995;Walls, Caines, Sanchez, & Khan, 2003).…”
Section: Yield Stress In Shear Rheology (Viscometry and Puv 1 Pd)mentioning
confidence: 99%
“…A measurement system such as the Hyperbolic Contraction Flow (HCF) technique, has been developed which is suitable for medium‐viscosity fluids (Stading & Bohlin, ; Wikström & Bohlin, ). This technique has been applied to various food systems such as dough/dairy products (Andersson, Öhgren, Johansson, Kniola, & Stading, ), bread (Oom, Pettersson, Taylor, & Stading, ), and ketchup (Berta, Wiklund, Kotzé, & Stading, ) as well as to polymer melts (Köpplmayr et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However these estimates are based on 2D videofluoroscopic images which quantify gross motion, not the flow within the bolus so it is not known whether the flow is turbulent (likely for lower viscosities) or "plug flow" -sliding as a coherent whole. Flow can be visualised in a lab using Doppler ultrasound [15]. Cohesiveness and surface tension for some materials can be derived from "capillary breakup elongational rheometry (CaBER)" -stretching a sample between two plates [16], [17].…”
Section: Research In Swallowing and Rheologymentioning
confidence: 99%
“…We wanted to explore further the possible uses of ultrasonic measurement principles to determine the rheological properties of drilling fluids. A similar study [7] in the food industries has shown very good results in characterizing another complex fluid, the well-known tomato ketchup, which is also non-Newtonian. Similar attempts have been made in characterizing slurries, another complex fluid found frequently in the process industries [8].…”
Section: Introductionmentioning
confidence: 88%